Optimalisasi Kinerja Dosen Perguruan Tinggi Swasta Program Studi Akuntansi Dan Manajemen di Provinsi Riau - Rijal, Af (Komunitas Manajemen Kompetitif, 2015)
Abstract: The purpose of this study was to determine the effect of leadership on organizational culture, influence of compensation on organizational culture, leadership influence on the performance of the lecturer, the effect of compensation on the performance of teachers and the influence of organizational culture on the performance of private college lecturer in Riau province. The whole object of research lecturer in Private University in three colleges namely Riau Islamic University (UIR), Lancang Kuning University (UNILAK) and the University of sand Pengaraian (UPP) at the Faculty of Economics and Management Studies Program Akuntasni totaling 68 people consisting of as many UIR 31 people, 25 and UPP UNILAK as many as 12 people with saturated sampling technique. The variables studied consisted of three independent variables and the dependent variable. The independent variable is leadership (X1), compensation (X2), and the culture of the organization, while the dependent variable is the performance of lecturers (Y). The method used in this study is a quantitative method. The results showed that the direct effect of leadership on organizational culture variables of 0.615. Then the variable compensation of organizational culture at 0.372. Leadership variables on the performance faculty at 0.174. Variable compensation on the performance faculty at 0.416 and variable influence of organizational culture on the performance faculty of 0,429. Then the variable indirect causal influence on the performance faculty leadership through organizational culture at 0.264 and compensation to the performance of 0,160 professors. Total causal influence of leadership on the performance of 0,438 professors, lecturers compensation to performance of 0.576 and organizational culture on the performance faculty of 0,429. Direct influence over the dominant variable affecting the compensation of faculty performance, but indirectly through the organizational culture of leadership that is greater than its effect on the performance of faculty compensation. Keywords: Leadership, compensation, organizational culture, faculty performance.